2019
DOI: 10.3390/cancers11050634
|View full text |Cite
|
Sign up to set email alerts
|

Perturbing Enhancer Activity in Cancer Therapy

Abstract: Tight regulation of gene transcription is essential for normal development, tissue homeostasis, and disease-free survival. Enhancers are distal regulatory elements in the genome that provide specificity to gene expression programs and are frequently misregulated in cancer. Recent studies examined various enhancer-driven malignant dependencies and identified different approaches to specifically target these programs. In this review, we describe numerous features that make enhancers good transcriptional targets … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 203 publications
(221 reference statements)
0
13
0
Order By: Relevance
“…In this section, we will therefore concentrate mainly on enhancer inhibitors affecting eRNA production to elucidate their potential therapeutic effects on inflammatory immune diseases and even cancer. The eRNA-related agents in cancer have been previously reviewed, including bromodomain and extra-terminal (BET) inhibitors, cyclin-dependent kinases (CDKs), HAT inhibitors and HDAC inhibitors ( 33 , 34 , 177 ). Since inhibitors that fully target eRNAs in inflammatory immune-related diseases have been rarely studied, the combined inhibitors of eRNAs and active enhancers, which produce eRNAs, have been summarized along with their therapeutic potential in inflammatory immune diseases in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we will therefore concentrate mainly on enhancer inhibitors affecting eRNA production to elucidate their potential therapeutic effects on inflammatory immune diseases and even cancer. The eRNA-related agents in cancer have been previously reviewed, including bromodomain and extra-terminal (BET) inhibitors, cyclin-dependent kinases (CDKs), HAT inhibitors and HDAC inhibitors ( 33 , 34 , 177 ). Since inhibitors that fully target eRNAs in inflammatory immune-related diseases have been rarely studied, the combined inhibitors of eRNAs and active enhancers, which produce eRNAs, have been summarized along with their therapeutic potential in inflammatory immune diseases in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, enhancer transcription analyses and eRNA generation processes revealed that TF modulators, HAT inhibitors and HDAC inhibitors influence eRNA and mRNA production by modulating enhancer epigenetic characteristics ( 177 ) ( Figure 4 ). HATs, such as p300-CBP, enable histone tail acetylation modifications ( 195 ), whereas polycomb repressive complex (PRC) mediates histone methylation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have linked nucleotide variations in enhancer-associated chromatin-modifying components to a number of phenotypic changes [ 11 , 12 ]. As reported, the absence of a SE can lead to under-expression of cancer associated genes and has profound effects on certain oncogenic properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cohen et al indicated that the change of epigenetic characteristics on enhancer elements is an important factor driving the formation of human colorectal cancer [ 12 ]. Accordingly, targeting aberrant enhancer components has become an effective therapeutic strategy on various cancers [ 8 , 11 ]. However, tremendous efforts remain to be invested to further clarify the mechanisms underlying enhancer-mediated processes in cancer and other diseases [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in chromatin, including changes in histone modifications or their modifying enzymes or changes in the expression or activity of chromatin remodelers due to genetic alterations, also frequently occurs in cancer, but are more poorly understood [11,12]. To date, most studies examining changes in histone modifications have largely been performed in cultured cells, precluding a clear interpretation of the clinical importance of these analyses.…”
Section: Introductionmentioning
confidence: 99%